KEPEDULIAN ORANG TUA DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN DI SMP NEGERI 2 KOTA MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aimed to describe the awareness of student’s parents in improving the quality of education in SMP Negeri 2 Kota Magelang of the focus was the response of student’s parents in improving the quality of education, the involvement of student’s parents in decision-making, implementation,research and the factors those contribute the greatest concern of parents of students in the program to improve the quality of education in SMP Negeri 2 Kota Magelang. This study was a qualitative-naturalistic study conducted to the SMP Negeri 2 Kota Magelang, Central Java. The data collection techniques were: participant observation, interviews, and documentation. The validity of the data were obtained through in-depth interviews and triangulation of data through sources. The analysis of the data was done with data reduction, data presentation, and conclusion. The results of the research showed that involvement of student’s parents in improving the quality of education in SMP Negeri 2 Kota Magelang was high enough. They involved from the planning phase to the implementation of supervision. To improve the quality of education, school has a strategy with appoint a coordinator from one of the student’s parent. Contribution of parents in the program of improving the quality of education included four aspects, those were planing, organizing, monitoring/supervising, and finance. The aspect that have the greatest contributed to the education quality improvement program was the financial aspect.